METHODS OF CLINICAL-MORPHOLOGICAL EXAMINATION OF CHRONIC TONSILLITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
During the research, 25 patients and 25 volunteer workers were selected for the control group, who applied to the ENT polyclinic of the Tashkent Medical Academy. Pathological microflora is found in the obtained smears, the phagocytic activity of leukocytes decreases, and multinucleated types of leukocytes appear in the blood, and lymphocytes decrease.